Stable clinical course in three siblings with late-onset isolated sulfite oxidase deficiency: a case series and literature review - Maoqiang Tian; Yi Qu; Lingyi Huang; Xiaojuan Su; Shiping Li; Junjie Ying; Fengyan Zhao; Dezhi Mu (BMC, 2019)
Abstract Background Isolated sulfite oxidase deficiency (ISOD) is an autosomal recessive disorder caused by a deficiency of sulfite oxidase, which is encoded by the sulfite oxidase gene (SUOX). Clinically, the disorder is classified as one of two forms: the late-onset mild form or the classic early-onset form. The latter is life-threatening and always leads to death during early childhood. Mild ISOD cases are rare and may benefit from dietary therapy. To date, no cases of ISOD have been reported to recover spontaneously. Here, we present three mild ISOD cases in one family, each with a stable clinical course and spontaneous recovery. Case presentation All three siblings had two novel compound heterozygous mutations in the SUOX gene (NM_000456; c.1096C > T [p.R366C] and c.1376G > A [p.R459Q]). The siblings included two males and one female with late ages of onset (12-16 months) and presented with specific neuroimaging abnormalities limited to the bilateral globus pallidus and substantia nigra. The three patients had decreased plasma homocysteine levels. They exhibited a monophasic clinical course continuing up to 8.5 years even without dietary therapy. Conclusion This is the first report of mild ISOD cases with a stable clinical course and spontaneous recovery without dietary therapy. Our study provides an expansion for the clinical spectrum of ISOD. Furthermore, we highlight the importance of including ISOD in the differential diagnosis for patients presenting with late-onset symptoms, bilaterally symmetric regions of abnormal intensities in the basal ganglia, and decreased plasma homocysteine levels.